Beyond Perceived Privilege: A Case Study of a Private School’s Views on Improving Inclusive Education - Anderson Leachman, Kishi (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2025)
⁠⁠⁠⁠⁠⁠⁠Inclusive education in private schools remains an under-researched area, particularly within the Caribbean. This qualitative single-case study explores the perspectives of 27 purposively selected stakeholders—including educators, parents, students, and support staff—at a private primary school in urban Jamaica. Through thematic analysis, key barriers to effective inclusion were identified: inconsistent communication, limited staff capacity, inadequate school—community partnerships, and insufficient human and physical resources. Despite these challenges, stakeholders expressed a strong commitment to improving inclusive practices, which are examined in this article. The findings underscore the importance of grounding inclusive education policy and practice in the lived experiences of those directly involved. While not generalizable, the study offers valuable insights that can inform inclusive education efforts in both private and public schools within comparable contexts.